Outcome and process accountability in negotiation: a motivated processing approach - Simões, E. (2011)
Past research indicate that negotiators under outcome accountability, compared to non-accountable ones, are more prone to competitive behavior which leads to suboptimal agreements, even when there is the possibility of obtaining higher joint gain. However, recent research showed that negotiators under process accountability made more accurate estimates of the other party’s preferences and interests and obtained higher joint gain than the non-accountable counterparts. Moreover, there’s some evidence that equality in gain sharing may be moderated by social motives. The current study with professional negotiators (N = 88) focus on the effects of both outcome and process accountability on the negotiation processes in a prosocial climate. Results indicate that accountable negotiators tend to maximize the agreement’s value, thus suggesting a positive influence of the interaction of these two variables on the negotiation’s outcomes and processes. Non-accountable negotiators and negotiators held accountable only for outcome tend to get lower gains than those obtained by the negotiators under process accountability, although they are prone to divide gains more equitably. Theoretical implications of these results as well as its consequences for the negotiation practice in organizations are discussed.